Comparative analysis of selected skeletons for dependency injection - Szewczyk, Rafał; Plechawska-Wójcik, Małgorzata (Journal of Computer Sciences Institute, 2018)
The article presents a comparative analysis of selected skeletons for dependency injection in Java. The analysis consists in comparing the speed of the frameworks in different configurations. For each technology has been created a separate application, and the results are presented in graphs and tables.